STUDENTS’ PERCEPTION ON USING ENGLISH WITH CoE FOR HOSPITALITY: A CASE STUDY IN UNIVERSITY OF MUHAMMADIYAH MALANG - Meta Nordiana; Masyhud - (Universitas Muhammadiyah Metro, 2026)
This study examines students' perceptions of English language use in the Hospitality Center of Excellence (CoE) program at the University of Muhammadiyah Malang, highlighting how these perceptions shape their professional development. Many students view English language proficiency as crucial for improving customer service skills, adapting to multicultural environments, and enhancing self-confidence. This study explores how English language skills impact students' internship experiences and career aspirations. This study employed a qualitative descriptive method. The participants consisted of three students from the English Language Education Department who participated in hospitality internships in different hotel divisions, namely front office and housekeeping. Data were collected through semi-structured interviews with three students who participated in hospitality internships in different hotel divisions. The data were analyzed using thematic analysis based on Miles, Huberman, and Saldaña’s interactive model, including data condensation, data display, and conclusion drawing. Findings revealed positive perceptions. Students recognized English as a valuable skill for facilitating communication with international guests, boosting self-confidence, and enhancing career readiness. However, challenges included difficulty understanding diverse accents and initial anxiety in a professional environment. Despite these obstacles, students demonstrated resilience, using tools such as Google Translate to aid communication. The results suggest that real-world experiences through internships complement classroom learning, enhancing students' adaptability and competitiveness in a global workforce.